Methyl Benzoate Is Superior to Other Natural Fumigants for Controlling the Indian Meal Moth (Plodia interpunctella) - Md Munir Mostafiz; Errol Hassan; Rajendra Acharya; Jae-Kyoung Shim; Kyeong-Yeoll Lee (Insects, 2020)
The Indian meal moth, Plodia interpunctella (Hübner) (Lepidoptera: Pyralidae), is an insect pest that commonly affects stored and postharvest agricultural products. For the control of insect pests and mites, methyl benzoate (MBe) is lethal as a fumigant and also causes contact toxicity; although it has already been established as a food-safe natural product, the fumigation toxicity of MBe has yet to be demonstrated in P. interpunctella. Herein, we evaluated MBe as a potential fumigant for controlling adults of P. interpunctella in two bioassays. Compared to the monoterpenes examined under laboratory conditions, MBe demonstrated high fumigant activity using a 1-L glass bottle at 1 μL/L air within 4 h of exposure. The median lethal concentration (LC50) of MBe was 0.1 μL/L air; the median lethal time (LT50) of MBe at 0.1, 0.3, 0.5, and 1 μL/L air was 3.8, 3.3, 2.8, and 2.0 h, respectively. Compared with commercially available monoterpene compounds used in pest control, MBe showed the highest fumigant toxicity (toxicity order as follows): MBe > citronellal > linalool > 1,8 cineole > limonene. Moreover, in a larger space assay, MBe caused 100% mortality of P. interpunctella at 0.01 μL/cm3 of air after 24 h of exposure. Therefore, MBe can be recommended for use in food security programs as an ecofriendly alternative fumigant. Specifically, it provides another management tool for curtailing the loss of stored food commodities due to P. interpunctella infestation.